Look Before You Leap: Improving the Users Ability to Detect Fraud in Electronic Marketplaces - Sänger, Johannes; Hänsch, Norman; Glass, Brian; Benenson, Zinaida; Landwirth, Robert; Sasse, Angela M. (SIGCHI Conference on Human Factors in Computing Systems, 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.lehrst.lookbe

Programming Experience Might Not Help in Comprehending Obfuscated Source Code Efficiently - Hänsch, Norman; Schankin, Andrea; Protsenko, Mykolai; Freiling, Felix; Benenson, Zinaida (Proceedings of the Fourteenth Symposium on Usable Privacy and Security, 2018)
UnivIS-Import:2018-09-06:Pub.2018.tech.IMMD.lehrst.progra

Specifying IT security awareness - Hänsch, Norman; Benenson, Zinaida (SHCIS14, 2014)
IT users are faced with various threats on a daily basis. Unfortunately, not all possible dangers are known to them, such that the users fall an easy victim to attacks. For this reason, IT specialists demand for higher IT security awareness. Although researchers and practitioners exercise ongoing efforts in this area, their work often lacks a concise definition of the term 'security awareness'. Since there is no agreement on the term, different (and sometimes not compatible) ways of raising and measuring security awareness exist. This paper is an effort to give an overview of this phenomenon and to show that awareness in IT security is not standardized yet.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lehrst.specif